2000
DOI: 10.1177/107484070000600305
|View full text |Cite
|
Sign up to set email alerts
|

Family Variables Associated With Well-Being in Siblings of Children With Down Syndrome

Abstract: The purpose of this research was to examine relationships among family demands, family resources, family problem-solving communication, family coping, and sibling well-being in 41 families of children with Down syndrome. The guiding framework for this research was the resiliency model of family stress, adjustment, and adaptation. Mailed questionnaires were completed by mothers and siblings closest in age to the children with Down syndrome. Results indicate that, as a group, the siblings in this study had favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 32 publications
4
50
1
7
Order By: Relevance
“…One-fourth of the 20 studies in this group identified a theoretical orientation. Fifteen percent [Lustig and Akey, 1999;Van Riper, 2000;Azar and Badr, 2006] cited a theory related to the work of McCubbin and coworkers McCubbin and McCubbin, 1993;McCubbin et al, 1996]. These articles all had theoretical inconsistencies among terminology, definitions, and theory.…”
Section: Conceptualizing and Measuring Outcomesmentioning
confidence: 93%
See 1 more Smart Citation
“…One-fourth of the 20 studies in this group identified a theoretical orientation. Fifteen percent [Lustig and Akey, 1999;Van Riper, 2000;Azar and Badr, 2006] cited a theory related to the work of McCubbin and coworkers McCubbin and McCubbin, 1993;McCubbin et al, 1996]. These articles all had theoretical inconsistencies among terminology, definitions, and theory.…”
Section: Conceptualizing and Measuring Outcomesmentioning
confidence: 93%
“…These articles all had theoretical inconsistencies among terminology, definitions, and theory. For example, Van Riper [2000] cited the guiding framework as the Resiliency Model [McCubbin and McCubbin, 1993] and defined its ''central concept'' (p. 269) as family adaptation [bringing ''. .…”
Section: Conceptualizing and Measuring Outcomesmentioning
confidence: 99%
“…Examining 41 siblings of children with Down syndrome, Van Riper [2000] found that siblings' increased levels of social competence related to higher amounts of family problem-solving communication, resources, and coping skills. Though not surprising, such findings within the group of siblings of children with Down syndrome can be helpful in screening and intervention efforts.…”
Section: Studies Focused On Families Of Persons With Down Syndromementioning
confidence: 98%
“…In other recent studies, the vulnerability of the family has been the focus into behavioral problems of the young child. Poor family cohesion, openly expressed family conflict and anger, parental disagreement, and poor family functioning have all been found to be associated with behavioral problems in children (Benzies et al, 2004;Dawson et al, 2003;du Rocher Schudlich & Cummings, 2007;Hughes et al, 2008;Kendall et al, 2005;Lucia & Breslau, 2006;Oravecz, Koblinsky, & Randolph, 2008;Shelton & Harold, 2008) while supportive family factors (family resources, family problem-solving communication) are linked to the well being of all family members (Van Riper, 2000). Focusing on ways to identify and support these families may prove useful in decreasing the number of preschool children with behavioral problems.…”
Section: Level Of Risk Of Having a Child With A Behavioral Problemmentioning
confidence: 99%